Non-Archimedean Kelvin Transformation - Antoniouk, A. V.; Kochubei, A. N. (Matematychni Studii, 2026)
We introduce and study an analog of the Kelvin transformation connected with the Vladimirov-Taibleson operator acting on real- or complex-valued functions on a space K^n over a non-Archimedean local field K.